"A publicidade fora do armário": a representação da comunidade LGBTQIA+ nas produções audiovisuais, abordada pelo experimento TUA VOZ - Greco, Stefany de Souza (Universidade do Vale do Rio dos Sinos, 2021)
This project aims to expose the perceptions and feelings of people belonging to the LGBTQIA + community, regarding brands that present and present an inclusive and activist discourse in their audiovisual campaigns and actions on social networks. Therefore, in addition to a deepening of the theoretical and empirical study, seeking to understand the entire trajectory of the LGBTQIA + community, this project explains these perceptions through the experimental methodology, in the construction of the documentary Tua Voz. This has been made through bibliographic research methodologies, quantitative research, field diary and experiment and an in-depth study of the narrative construction of documentaries and their different types. After the execution of the experiment, through the construction of the documentary, the results presented that the actions of brands that explore the points of diversity impact much more than we imagine in the social construction of each individual, whether or not they belong to the LGTBQIA + community.
Keywords: LGBTQIA+; Cinema; Audiovisual; Documentário; Ativismo de marcas; Movie theater; Audio-visual; Documentary; Brand activism